Feasibility and Design of Grid-connected Floating PVs in West Java, Indonesia - Iskandar, Handoko Rusiana; Iman, Agnia; Daelami, Ahmad (Elektron : Jurnal Ilmiah, 2023)
The modeling and design of grid-connected floating photovoltaic (PV) are covered in this paper. Using dams in West Java as a location with present floating PV potential, this paper encourages the development of renewable energy and the construction of fossil-free power plants in various parts of Indonesia. Three alternative locations—the Saguling, Cirata, and Jatiluhur dams—are proposed for floating-PV type designs, each having a capacity of 1 MW grid-connected. The modeling process uses a variety of dependable auxiliary software to simulate possible solar energy use as well as capacity design optimization of system components. Modeling and simulation findings indicate that the grids of the Saguling, Cirata, and Jatiluhur dam have a combined potential for electrical energy of 1705.2 MWh/year, 1635.4 MWh/year, and 1611.8 MWh/year, respectively, with an average performance ratio of 0.74 to 0.75. The total PV capacity for each dam is 1197 Wp, using 550 Wp/PV panel with an efficiency 21.51%/PV and 4 Inverters for grid connectivity. There are 544 PV units per array. 5561 m2 is the estimated area needed to build this system.